Implications of tumor-positive sentinel lymph nodes in single vs multiple nodal basins in melanoma - Reyes, Emiliano; Lourdault, Kristel; Ramiscal, Judi Anne; Stern, Stacey; Essner, Richard (Frontiers in Oncology, 2024)
Background Melanoma patients’ prognosis is based on the primary tumor characteristics and the tumor status of the regional lymph nodes. The advent of lymphoscintigraphy with SLN biopsy (SLNB) has shown that melanoma can drain to multiple nodal basins but the significance of multiple basins (vs. one basin) with tumor-positive sentinel lymph node(s) (+SLN) of similar tumor burden has not been shown. We examined the impact of the number of nodal basins with +SLN (+basin) in melanoma patients and its significance for patients’ prognosis and survival. Study design We identified 1,915 patients with +SLN from two randomized surgical clinical trials: Multicenter Selective Lymphadenectomy Trials I and II. Patient groups were divided based on number of +SLNs and number of +basins. Disease-free survival (DFS), distant disease-free survival (DDFS) and melanoma-specific survival (MSS) were compared with the Kaplan-Meier method and log-rank tests. Univariable and multivariable analyses were performed using Cox proportional hazard regressions. Results Among the 1,915 patients, 1,501 had only one +SLN (78%) in one basin and 414 (22%) had multiple +SLNs: 340 located in one basin and 74 in multiple basins. Among patients with multiple +SLNs, those with multiple +basins have a worse DFS, DDFS and MSS than those with a single basin (p ≤ 0.0001 for all comparisons). MSS was significantly different based on AJCC stages: AJCC IIIA and IIIB (p ≤ 0.001 and 0.0287, respectively). Conclusion Our results suggest that the number of tumor-positive basins may be important for staging and in understanding the biology of lymph node metastases.